Judgment Day - Jenkins, Jerry B.; Fabry, Chris, 1961-; LaHaye, Tim F. (Wheaton, Ill. : Tyndale House Publishers, 2001)
In the aftermath of the Lamb earthquake, Judd and Vicki of the Young Trib Force search for a place to hide from the ruthless pursuit of the Global Community.
4.3
5-8
Keywords: Christian life -- Juvenile fiction; End of the world -- Juvenile fiction; Good and evil -- Juvenile fiction; Christian life -- Fiction; End of the world -- Fiction; Good and evil -- Fiction; Christian fiction; Christian life -- Fiction; End of the world -- Fiction; Good and evil -- Fiction; Religious fiction; Fantastic fiction; Fantastic fiction; Religious fiction